Prank gone wrong, transverse colon perforation due to air compressor pipe placed in anus - Suraj, Lisha; Shaikh, Tanveer (International Journal of Research in Medical Sciences, 2017)
Colonic perforation and pneumoperitoneum are the most commonly seen complications in cases of air entry into rectum at a high velocity in a short duration of time. Here we present a case of 24-year-old male who was brought to our emergency department with severe abdominal pain and distension for 2 hours. History suggestive of prank that went wrong, when somebody pumped high-pressure air from an air compressor into his anus while he was changing his clothes. The physical examination and investigations were suggestive of free gas in peritoneal cavity and the patient was taken for emergency exploratory laparotomy. On exploration, gaseous distention of whole colon was observed with serosal tear all along the colon with fresh bleeding. A rent of 1x1 cm seen in middle of transverse colon. The defect was closed primarily and a diverting loop ileostomy was made. Several number of cases of Air compressor abuse has been reported in literature as it is one of the non-iatrogenic cause of barotrauma to colon. It is usually seen when friends play prank on each other.